Growth and yield responses of BARI Gom-25 in relation to sowing time - Jahan, Nargis; Adam, AMM Golam (Dhaka University Journal of Biological Sciences, 2015)
Abstract not available Dhaka Univ. J. Biol. Sci. 24(1): 99-102, 2015 (January)